Permasalahan Upah dalam Hukum Ketenagakerjaan Indonesia: Analisis Implementasi UU No. 13 Tahun 2003 dan Dampak UU No. 6 Tahun 2023 tentang Cipta Kerja - Agip Herliagi; Febi Afifah Mugiri; Putri Fatimah Zahra; Heriyanto Heriyanto (Journal of Innovative and Creativity, 2025)
The development of the Indonesian people as a whole plays a very important role for the future of the nation and state, this is also inseparable from the development of employment which is an integral part of national development based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Employment is one of the important aspects in people's lives. Fair and decent wages are one of the basic rights of workers that must be fulfilled. However, in practice, there are still problems related to the fulfillment of decent wages for workers in industrial relations. This study aims to analyze wage issues in labor law in Indonesia, especially in the context of the implementation of Law Number 13 of 2003 concerning Manpower and its impact after the enactment of Law Number 6 of 2023 concerning Job Creation. The focus of the study includes the normative aspects of wage law, the gap between policy and practice, and legal protection for workers in obtaining a decent income. This study uses a normative juridical method with a legislative and conceptual approach. The research results show that wage regulation in Indonesia still faces various problems, such as disparities between regions, violations of minimum wage provisions, weak law enforcement, and unequal bargaining positions between workers and employers.